2015 IEEE International Conference on Software Maintenance and Evolution (ICSME) 2015
DOI: 10.1109/icsm.2015.7332450
|View full text |Cite
|
Sign up to set email alerts
|

Investigating naming convention adherence in Java references

Abstract: Abstract-Naming conventions can help the readability and comprehension of code, and thus the onboarding of new developers. Conventions also provide cues that help developers and tools extract information from identifier names to support software maintenance. Tools exist to automatically check naming conventions but they are often limited to simple checks, e.g. regarding typography. The adherence to more elaborate conventions, such as the use of noun and verbal phrases in names, is not checked.We present NOMINA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…He investigates the structure of Java class names and identifies common naming patterns. Butler et al [10] conduct a survey of the forms of Java reference names and then use the study outcome to investigate naming convention adherence in Java references [41]. Arnaoudova et al [42,43] defined source code Linguistic Antipatterns (LAs) that discuss poor practices in naming and choice of identifiers and defined a catalog of 17 types of LAs related to inconsistencies.…”
Section: Standards For Methods Namesmentioning
confidence: 99%
“…He investigates the structure of Java class names and identifies common naming patterns. Butler et al [10] conduct a survey of the forms of Java reference names and then use the study outcome to investigate naming convention adherence in Java references [41]. Arnaoudova et al [42,43] defined source code Linguistic Antipatterns (LAs) that discuss poor practices in naming and choice of identifiers and defined a catalog of 17 types of LAs related to inconsistencies.…”
Section: Standards For Methods Namesmentioning
confidence: 99%
“…Sridhara et al [30] generate descriptive summary comments for Java methods. Besides those work, some studies analyze the project source code and apply its abstract syntax tree information to code or document search [31][32][33][34][35][36][37]. In this paper, we use 7 kinds of features to represent our learning example and train our classifier.…”
Section: Related Workmentioning
confidence: 99%
“…Allamanis et al [3] reported that code reviewers often suggest to modify identifier names before accepting a code patch. Thus, in recent years, naming convention of program identifiers drew significant attention for improving program understanding and maintenance [3,6,13,27,32,48]. Among the identifiers, a good method name is particularly helpful because they often summarize the underlying functionalities of the methods [4,19].…”
Section: Related Workmentioning
confidence: 99%